RUANG WAKTU RITUAL DAN DESAIN INTERIOR - Santosa, Imam (Institute of Research and Community Outreach - Petra Christian University, 2005)
The journey of history is always followed by a mass change that produces new phenomena as the spirit of the age. In this metamorphic context%2C the human space always undergoes changes in its meaning throughout the age. The change of views towards space is then interpreted into a design work with unique characters because apart from truly holding on to the cultural value valid%2C it also moves towards aesthetic idioms with a relative parameter. Thus%2C as an attempt to reconstruct the way of thought that is now in the arrangement of the global cultural cross domain%2C it is a necessity to reminisce the comprehension of the essence of space as the core of the problems in interior designing. The acknowledgement and the search of truth in good design truly need to be practiced because with the essence of truth%2C design will always extend and develop according to the context of its time. Abstract in Bahasa Indonesia : Perjalanan sejarah selalu diikuti oleh perubahan masa yang menghasilkan suatu fenomena baru sebagai spirit zaman. Dalam konteks perubahan tersebut ruang manusia selalu mengalami pergeseran makna seiring perjalanan zaman. Pergeseran pandangan terhadap ruang%2C kemudian diterjemahkan ke dalam wujud karya desain dengan berbagai keunikan%2C karena disamping berpegang teguh kepada nilai budaya yang berlaku%2C juga mengacu kepada idiom-idiom estetika dengan parameter yang relative. Untuk itu perlu merenungi kembali pemahaman tentang hakekat ruang sebagai inti dari persoalan desain interior sebagai upaya merekonstruksi kembali kerangka pemikiran yang kini berada dalam domain persilangan budaya global. Penelusuran dan perncarian kebenaran dalam tatanan good design%2C merupakan suatu yang perlu terus dilakukan%2C karena dengan hakikat kebenaran%2C desain akan selalu tumbuh dan berkembang sesuai konteks zamannya. space%2C time%2C ritual%2C interior design.